2020
DOI: 10.1051/0004-6361/201936143
|View full text |Cite
|
Sign up to set email alerts
|

Colors and patterns of black hole X-ray binary GX 339-4

Abstract: Black hole X-ray binaries show signs of nonthermal emission in the optical to near-infrared range. We analyzed optical to near-infrared SMARTS data on GX 339-4 over the 2002–2011 period. Using soft state data, we estimated the interstellar extinction toward the source and characteristic color temperatures of the accretion disk. We show that various spectral states of regular outbursts occupy similar regions on color-magnitude diagrams, and that transitions between the states proceed along the same tracks despi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 112 publications
(150 reference statements)
2
7
0
Order By: Relevance
“…Therefore, the 2017-2018 X-ray outburst of GX 339−4 seems to follow a relatively typical evolution when compared to the Xray behaviour of both hard-only and successful outbursts, with no preliminary indicators that may identify whether an outburst is successful or not. A similar result was also found during detailed nearinfrared (NIR) and optical studies of outbursts from BH LMXBs (Kosenkov et al 2020), where no indicators in the NIR/optical colours or magnitude were identified that might allow for an identification of a hard-only or successful outburst.…”
Section: Comparison With Other Outburstssupporting
confidence: 78%
“…Therefore, the 2017-2018 X-ray outburst of GX 339−4 seems to follow a relatively typical evolution when compared to the Xray behaviour of both hard-only and successful outbursts, with no preliminary indicators that may identify whether an outburst is successful or not. A similar result was also found during detailed nearinfrared (NIR) and optical studies of outbursts from BH LMXBs (Kosenkov et al 2020), where no indicators in the NIR/optical colours or magnitude were identified that might allow for an identification of a hard-only or successful outburst.…”
Section: Comparison With Other Outburstssupporting
confidence: 78%
“…In particular, we find that the scenario where optical emission originates from the jet base and the IR emission originates from the particle acceleration region z diss is consistent with the data. An alternative scenario is that both the IR and the optical emission originate in a hot flow that consists of thermal and non-thermal electrons (Poutanen & Veledina 2014 ;Kosenkov et al 2020 ), a scenario that better describes the soft states (Kosenkov & Veledina 2018 ). Further simultaneous IR-to-optical observations in the hard state would be able to test this scenario, as well as simultaneous polarization measurements across the entire optical/IR band (although see e.g.…”
Section: Multiwavelength Spectrum and Jetmentioning
confidence: 99%
“…In particular, we find that the scenario where optical emission originates from the jet base and the IR emission originates from the particle acceleration region 𝑧 diss is consistent with the data. An alternative scenario is that both the IR and the optical emission originate in a hot flow that consists of thermal and non-thermal electrons (Poutanen & Veledina 2014;Kosenkov et al 2020), a scenario that better describes the soft states (Kosenkov & Veledina 2018). Further simultaneous IR-to-optical observations in the hard state would be able to test this scenario, as well as simultaneous polarisation measurements across the entire optical/IR band (although see e.g., Russell & Fender 2008 for measurements prior to the 2010 outburst).…”
Section: Multi-wavelength Spectrum and Jet Dynamicsmentioning
confidence: 99%